Ricardo Palma, correcto funcionario público - Varillas Montenegro, Alberto (2018)
From very young, Ricardo Palma was an efficient civil servant among the disorganized system that govern the public administration from then. For many years he was the Body Politic Officer of the Peruvian Army, speciality that nowadays is known as Administration; for two years he was assigned to the consular service, but in this sector he didn’t get to hold any post; for four years he was Personal Secretary of the President while he worked, also, as Senator for the Loreto region; finally, since 1883 until the end of his days–30 years–he was Director of the National Library of Peru. In moments where, unfortunately, the Peruvian public administration goes through a moment of a dreadful loss of prestige, it’s worth to highlight that Palma dedicate his useful life to the service of the Peruvian State and passed away without any exterior sign of wealth.